Diseño y operacionalización de un sistema crediticio para los integrantes de la organización de los Saraguros residentes en Quito. Caso: "Saruqllakta" - Lozano Lozano, Luis Antonio (2007)
One of the main problems of the domestic financial system is that, even with a great technology, good infrastructure, have failed to reach the large number of individuals mainly farmers and traders, who lack a working capital and need access a type of credit. As part of the problem, it is necessary to establish a new credit system dedicated to independent producers and traders, is why an alternative credit system fully operational and is applicable not only for the sector in question is posed, but also for other sectors with similar features.